2019
DOI: 10.1093/pcp/pcz127
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Arabidopsis ROOT UVB SENSITIVE4 Disrupts Anther Dehiscence by Suppressing Secondary Thickening in the Endothecium

Abstract: ROOT UV-B SENSITIVE4 (RUS4) encodes a protein with no known function that contains a conserved Domain of Unknown Function 647 (DUF647). The DUF647-containing proteins RUS1 and RUS2 have previously been associated with root UV-B-sensing pathway that plays a major role in Arabidopsis early seedling morphogenesis and development. Here, we show that RUS4 knockdown Arabidopsis plants, referred to as amiR-RUS4, were severely reduced in male fertility with indehiscent anthers. Light microscopy of anther sections reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Both RUS1 and RUS2 were also independently identified in a weak-auxin response genetic screen, suggesting that RUS1 and RUS2 regulate plant development by directly or indirectly affecting auxin distributions [ 9 , 10 ]. Recently, a knockdown study of RUS4 via artificial microRNA (amiR) suggested that RUS4 plays a role in Arabidopsis reproductive development [ 18 ]. While homozygous rus4 knockout mutants showed no obvious phenotype in their study and ours, down-regulation of RUS4 mRNA by the amiR approach disrupted anther dehiscence, likely through the down-regulation of genes such as NST1 and NST2, which are known to play roles in secondary cell wall thickening in the Arabidopsis anther endothecium [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both RUS1 and RUS2 were also independently identified in a weak-auxin response genetic screen, suggesting that RUS1 and RUS2 regulate plant development by directly or indirectly affecting auxin distributions [ 9 , 10 ]. Recently, a knockdown study of RUS4 via artificial microRNA (amiR) suggested that RUS4 plays a role in Arabidopsis reproductive development [ 18 ]. While homozygous rus4 knockout mutants showed no obvious phenotype in their study and ours, down-regulation of RUS4 mRNA by the amiR approach disrupted anther dehiscence, likely through the down-regulation of genes such as NST1 and NST2, which are known to play roles in secondary cell wall thickening in the Arabidopsis anther endothecium [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a knockdown study of RUS4 via artificial microRNA (amiR) suggested that RUS4 plays a role in Arabidopsis reproductive development [ 18 ]. While homozygous rus4 knockout mutants showed no obvious phenotype in their study and ours, down-regulation of RUS4 mRNA by the amiR approach disrupted anther dehiscence, likely through the down-regulation of genes such as NST1 and NST2, which are known to play roles in secondary cell wall thickening in the Arabidopsis anther endothecium [ 18 ]. In this study, our detailed genetic and molecular characterization of two knockout mutants for RUS6 , rus6-1 and rus6-2 , clearly identified an indispensable role of RUS6 in Arabidopsis embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…AtRUS1 / WXR3 ( WEAK AUXIN RESPONSE 3 ) and AtRUS2 / WXR1 have functions involved in very-low fluence (VLF) UVB responses and vitamin B6 (VB6) homeostasis 17 19 , or regulation of polar auxin transport 20 , 21 . Recently, Arabidopsis RUS4 was reported to play a role in male fertility 22 , and RUS6 in early embryo development 23 . However, no leaf rolling phenotype of AtRUS / WXR genes has been reported in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%
“…RUS1 and RUS2, also named WXR3 (WEAK AUXIN RESPONSE 3) and WXR1 respectively, were independently identified for their roles in polar auxin transportation (Ge et al 2010;Yu et al 2013). More recently, Arabidopsis RUS4 was reported to play a role in male fertility through anther dehiscence by suppressing secondary thickening in the endothecium (Zhao et al 2019). Bioinformatic analyses suggest that RUS genes are broad-ly distributed in almost all eukaryotes, including plants, fungi and animals (Leasure et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro expressed proteins for both RUS1 and RUS2 appeared to be rapidly degraded and the attempts to characterize them were thus unsuccessful (Leasure et al 2009). The expression of RUS proteins in published reports was detected indirectly either through GFP fluorescence or yeast two-hybrid systems (Tong et al 2008;Leasure et al 2009;Ge et al 2010;Yu et al 2013;Zhao et al 2019). The biochemical characterizations of RUS proteins require a protein expression system which allows the heterologously expressed proteins to be solubilized, renatured and purified.…”
Section: Introductionmentioning
confidence: 99%